Adverse Effects of 5th Generation Mobile Technology on Flora and Fauna: Review Study. Issue 1 (March 2021) - Kumar, Rajesh; Geleta, Rabira; Pandey, Amit; Sinwar, Deepak
Abstract: Technology plays a very vital roles in the growth of the economy of any nation. Hence, information communication channel needs to be very strong for timely delivery of information and growth of any country. Mobile technology is the backbone of communication channel in any country who has incorporated it. Since 1980 mobile communication is very popular mode of communication and researches are going on in this area since that time. Starting from the first generation mobile network to fifth generation mobile network, every nation wants to enhance their information communication technology infrastructures in aspect of communication. The 5G mobile technology is subject of debate now a day. Still, most of the countries are in the race for adopting this technology and are ignoring its adverse effects on human health and environments. 5G mobile technology uses millimetre waves and higher frequency band 6 GHz to 100 GHz for communication. Initially, there was appeal made in United Nation Council and later in European Union against the launch of 5G, which was signed by more than three hundred scientists and doctors, stating that the 5G mobile technology is not good for environment. Various research has been conducted regarding the adverse effects of RF-EMF waves, which are generated by cell towers, on human health and environment. 5G uses very dense infrastructure and there is evidence that the RF-EMF radiation level is very strong in fifth generation mobile technology as compare to previous mobile technologies. Hence, the current study is focused on reviewing the impact of 5G mobile technology on flora and fauna Kingdome.